2010
DOI: 10.5188/ijsmer.17.211
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction Ability of Thiacalix[6]arene Derivatives from Rare Metal Mixed Solution

Abstract: In this study, a synthesis and extraction capability of two new thiacalix [6]arene (TC[6]A) derivatives modified at the lower or upper rims, which are TC[6]A-CH 2 CONEt 2 (1) and TC[6]A-CH 2 SCOCH 3 (2), respectively, will be discussed. The metal extraction properties of 1, 2, and TC[6]A (3), from automotive catalyst residue solution containing platinum-group metal cations (PGM solution) have been investigated. Compound 3 shows highest extraction capability for Zr cation which is ca. 87% (in pH 4.0 PGM solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Compounds p-tert-butylthiacalix [4]arene (2), p-tertbutylthiacalix [6]arene (3), p-tert-butyl-tetrakis[(dimethyl (thiocarbamoyl))oxy]thiacalix [4]arene (4) and p-tert-butylhexakis[(methylcarboxyl)oxy]thiacalix [6]arene (5) were synthesised according to literature methods (5,(32)(33)(34). As shown in Scheme 3, the synthesis of p-diethylaminomethylthiacalix [4]arene 1 proceeds as follows.…”
Section: Synthesis Of Extractantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds p-tert-butylthiacalix [4]arene (2), p-tertbutylthiacalix [6]arene (3), p-tert-butyl-tetrakis[(dimethyl (thiocarbamoyl))oxy]thiacalix [4]arene (4) and p-tert-butylhexakis[(methylcarboxyl)oxy]thiacalix [6]arene (5) were synthesised according to literature methods (5,(32)(33)(34). As shown in Scheme 3, the synthesis of p-diethylaminomethylthiacalix [4]arene 1 proceeds as follows.…”
Section: Synthesis Of Extractantsmentioning
confidence: 99%
“…Many functionalised thiacalix[n]arenes have been used for solvent extraction of alkali and transition metals (5, 6, 12 -20). Recently, we reported the synthesis and extraction capability of new, modified thiacalix [6]arene derivatives, in which the lower or upper rim was modified with a ZCH 2 CONEt 2 group or a ZCH 2 SCOCH 3 group, respectively (6). The extraction of Pt(IV), Pd(II) and Rh (III) ions from a spent automotive catalyst residue solution containing PGMs was very high using thiacalix [6]arene-CH 2 SCOCH 3 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Traeger et al (2012a,b) developed many acyclic sulfur-based extractants and explained their advantages over commercial extractants (Traeger et al, 2012a,b). On the other hand, thiacalix[n]arenes (n = 4, 6, and 8), are macrocyclic compounds, have high affinities for alkali, transition, and lanthanide metal ions, and are used for PGM separation (Itoh et al, 2010;Rajiv Gandhi et al, 2014;. In our previous work, we have reported that 5,11,17,23,29,35-tert-butyl-37,38,39,40,41,42-(dimethylthiocarbamoyl)oxy thiacalix[6]arene (1), 5,11,17,23-tert-butyl-25,26,27,28-(dimethylthiocarbamoyl)oxy thiacalix[4]arene (2), and p-tert-butylthiacalix[4/6]arenes (3 and 4) extract very high amounts of Pd(II) ions in a pH range of 3-4 from single-metal solutions and from diluted solutions of acidic leached automotive catalyst residues (Rajiv .…”
Section: Introductionmentioning
confidence: 99%